Effect of Hydroxide-Based Ionic Liquids on the Determination of Available Phosphorus in Alkaline Soils - Zhixiong LI; Zhenchao LIU; Qianshu LU; Chengzhong HE; Song ZHANG; Jinjiang YANG; Liankai ZHANG (Yankuang ceshi)
The level of available phosphorus in soil significantly impacted plant growth, soil fertility, and agricultural productivity. However, in alkaline soils, phosphorus mobility was low and was often tightly bound to minerals and organic matter, complicating the extraction process. Traditional extractants such as hydrochloric acid, ammonium fluoride, and sodium bicarbonate exhibited variability in extraction efficiency, affecting the accuracy of available phosphorus measurements in soil. Recent research on novel extractants focused on combining different chemicals to improve extraction efficiency and measurement accuracy. In this study, inductively coupled plasma-optical emission spectrometry (ICP-OES) was employed to determine available phosphorus in alkaline soils, and the effects of sodium hydroxide (NaOH) and cetyltrimethylammonium (CTA) as a mixed extractant were explored. The experimental results indicated that the addition of CTA facilitated interactions between phosphorus and water molecules or other ions in solution, thereby enhancing phosphorus solubility and extraction efficiency. Under optimized experimental conditions, the mixed extractant demonstrated significant advantages in improving the accuracy and efficiency of available phosphorus determination in alkaline soils. Additionally, the mixed extractant also showed effective extraction for neutral (NSA-4) and acidic (NSA-5) soil samples. These results suggested that the new mixed extractant had potential for broad applicability and promising prospects in the determination of available phosphorus in soils.